An FPGA-Based SoC Accelerator for Ant Colony Optimisation in Bearings-Only Target Motion Analysis - Deliparaschos, Kyriakos M.; Setola, Roberto; Oliva, Gabriele (My University, 2025)
Bearings-only Target Motion Analysis (BOTMA) is a challenging problem in signal processing due to its nonlinear nature and reliance on noisy angular measurements. Traditional iterative methods, such as Maximum Likelihood Estimation (MLE), are computationally demanding and sensitive to initialization. This paper presents a novel approach integrating Ant Colony optimisation (ACO) with a System-on-Chip Field Programmable Gate Array (SoC FPGA) to efficiently solve the MLE problem in BOTMA. The implementation is deployed on the PYNQ-Z1 platform, featuring an AMD Zynq-7000 SoC FPGA, which combines an ARM processing system with programmable logic. The FPGA design uses the hardware's concurrent processing capabilities to accelerate the ACO algorithm, achieving low-latency and high-throughput performance. The proposed solution is validated through simulations, demonstrating improved execution performance and low power consumption compared to the software model executed on a general-purpose processor. This work highlights the effectiveness of integrating advanced optimisation techniques with an FPGA-based SoC platform, enabling real-time BOTMA applications in resource-constrained environments.
Keywords: SoC FPGA; High-Level Synthesis (HLS); Target Motion Analysis; Ant Colony optimisation